INTEGRASI PEMBELAJARAN AL-QUR’AN HADITS DALAM KONTEKS SAINS DAN ILMU SOSIAL: INTEGRATION OF AL-QUR'AN HADITH LEARNING IN THE CONTEXT OF SCIENCE AND SOCIAL SCIENCE - Murtadlo, Ghulam; Pranada, Ahmad Rizki; Hidayati, Alfina; Fransiska, Devi; Ananda, Nabil Bintang; Sari, Putri Alam (CV. Kalimasada Group, 2023)
This study investigates the importance of integrating social sciences, scientific knowledge, and religious education into Indonesia’s education system. It aims to produce reliable scientific materials with a strong spiritual foundation while seamlessly combining general and religious education. Using a library research method, the study finds that separating religious and general knowledge can lead to inadequate teaching and scholars who are less aware of social issues. Careful integration of these fields enhances students’ understanding of science, society, and religion, fostering a more holistic education. The study recommends collaboration between the government, educational institutions, and experts to develop an integrative educational approach, contributing to the advancement of holistic education in Indonesia